MODEL PENCEGAHAN PRAKTIK KARTEL IMPOR DAGING SAPI DIKAITKAN DENGAN DAYA BELI MASYARAKAT - Riyadi, Idang; Syamsah, T.N (Magister Ilmu Hukum Sekolah Pascasarjana Unida, 2018)
The ability of consumer purchasing power of beef after cartel practice is the effect of the increase of beef price to consumer behavior varies, among others there are buy in fixed amount before and after price increase, there is a decrease the quantity of purchase and some are switching to consume chicken meat. Legal protection is preventively applied to provide legal protection and legal certainty for consumers so that with the prevention of the government in making policy or drafting legislation more carefully so that the interests of consumers or the wider community is not neglected. The purpose of this study is to discuss how to regulate beef imports in Indonesia, the implementation of beef imports categorized as cartels, as well as legal protection for consumers of beef as a result of the practice of imported cartels. The research method used in this research is the normative juridical approach, namely the law is conceptualized as norms, rules, principles or dogmas / jurisprudence. The results of this research are: 1) The regulation on beef import trade in Indonesia has undergone many changes following the market condition, 2) The form of violation of beef import trade in Indonesia occurring in Jabodetabek area is a cartel practice violating Article 11 of Law no. 5 Year 1999, 3) Business activities are not always done honestly by business actors. The act of business actor is not infrequently to the consumer, it is necessary to protect the consumers rights.